The combined utility of eye-tracking technology and cued retrospective think-aloud to investigate cognitive-perceptual mechanisms underpinning the visual gaze behaviours of climbing coaches - Mitchell, J.; Sheffield, D.; Taylor, N.; Giles, D.; Frances, A. M. (BASES Conference 2024, 2024)
Sports coaching by nature is vision-intensive, requiring sports coaches to perceive, interpret and evaluate complex, dynamical, and ambiguous visual information in time-pressured environ ments (Gegenfurtner, et al., 2023, Re-theorising learning and research methods in learning research, 142-158). Expert coaches demonstrate superior perceptual-cognitive skill through the use of extensive domain-specific knowledge to extrapolate key informa tion from their environment and, subsequently, make better, more efficient decisions (Mann, et al., 2007, Journal of Sport and Exercise Psychology, 29, 457-478). This study aimed to investigate the cognitive-perceptual mechanisms that underpin visual expertise in the observational analysis of climbing performance. Using a novel and previously underutilised methodological approach, the study combined eye-tracking and cued retrospective think aloud to capture the visual gaze behaviours, and their underpin ning cognitions, that define visual expertise in climbing coaching. With institutional ethics approval, 61 coaches (20 expert, 21 inter mediate, 20 novice) were asked to view video footage of 9 inter mediate boulderers (2 females; 7 males) and analyse the quality of their performance. During the coach`s analysis of the climber`s performance, eye-tracking recorded the coach`s gaze behaviour (fixation count, fixation duration, fixation location) to identify which aspects of the climber`s performance coaches attended to most frequently. Eye-tracking data was subsequently utilised as the basis for cued retrospective think-aloud (CRTA) interviews, whereby coaches were asked to retrospectively verbalise what aspects of the climber`s performance they were attending to during their analysis, using a replay of the climber`s performance with the coach`s eye-tracking data overlaid to stimulate discussion. CRTA data was analysed using inductive thematic analysis. The resulting eye-tracking data identified notable expertise-based dif ferences in the areas of interest most attended to by coaches. CRTA data provided further explanation as to the cognitive perceptual mechanisms underpinning the coaches` visual search strategy. Expert coaches were more cognizant of their visual search strategy and able to extract a greater level of detail when compared to their lesser experienced counterparts. CRTA data further elicited specific gaze strategies employed by coaches, such as the use of visual spots, visual pivots, and gaze anchors. Through complex domain-specific knowledge structures and learned visual practices, expert coaches actively focus on the most relevant aspects of a climber`s performance for analysis. The findings demonstrate the utility of combining eye-tracking and CRTA interviewing as a new, efficient methodology of capturing the cognitive-perceptual processes underpinning coaching expertise, and a valid and reliable source of data to inform coach education initiatives